Alfvénic fluctuations measured by in-vessel Mirnov coils at the Wendelstein 7-X stellarator. (11th November 2020) - Rahbarnia, K; Thomsen, H; Schilling, J; vaz Mendes, S; Endler, M; Kleiber, R; Könies, A; Borchardt, M; Slaby, C; Bluhm, T; Zilker, M; Carvalho, B B; et al.
Abstract: The magnetic diagnostic system at the optimized stellarator experiment Wendelstein 7-X (W7-X) includes a total number of 125 Mirnov coils, which are mounted at the inner plasma vessel wall. A wide range of expected signal amplitudes, frequencies and mode numbers is covered to account for the complex three-dimensional geometry of W7-X. The performed amplitude and phase calibration of individual coils including all relevant data acquisition system components allows a detailed spectral and mode analysis. The damped multiple signal classification method and stochastic system identification techniques are shortly described and applied. Two observations are emphasized within this work. Firstly, independent of magnetic configuration and heating scenario (electron cyclotron resonance heating and/or neutral beam injection), broadband fluctuations around 180 kHz have been measured. The nature of these fluctuations is possibly associated with ellipticity-induced Alfvén eigenmodes in the outer regions of the plasma. The latter was inferred by studying corresponding theoretically predicted Alfvén continua calculated with the 3D-MHD continuum code CONTI. Secondly, fast collapses of plasma current and energy, which occurred during recent operational phases at W7-X, show a clear magnetic signature. Short time scale Alfvénic bursts are revealed, which are induced during these sawtooth-like collapses.